Restructuring, consolidation and competition in Latin American banking markets - Yildirim, H. Semih; Philippatos, George C. (Journal of Banking & Finance, 2007)
This study examines the competitive conditions in the banking industries of eleven Latin American countries for the period 1993–2000. For these countries, the time interval under examination corresponds to an era characterized by substantial reforms to restructure their banking systems, increased consolidation and foreign bank penetration. The banks in our sample are found to be earning their revenues as if operating under monopolistic competition, as in many other developed and emerging financial systems. The results indicate that, overall, market concentration is not significantly related with competitive conduct. At the country level, however, we do observe a decline in competition for Brazil, Chile, and Venezuela in late 1990s which may be attributable to increased consolidation. Further, we observe that deregulation and opening up of the financial markets for foreign participation serves as an important catalyst to increase the competitiveness of banking markets. Higher degree of competition in the sector, in return, is associated with reduced bank margins and profitability but improved cost efficiency.